Weight, Stigma, and Attitudes toward Immigrants - Andrea Fazio; Matilde Giaccherini (Global Labor Organization (GLO), 2024)
Building on social identity theory, we suggest that natives from stereotyped groups tend to value cultural distance more and think that immigrants are not good for the economy and the fiscal system. We draw upon research showing that overweight and obese individuals suffer from social stigma and discrimination and we investigate the relationship between high body mass and attitudes toward immigrants in Europe. We exploit the appointment of the Belgian Minister of Health to provide causal evidence that stigmatization and stereotyping contribute to negative attitudes toward immigrants. Furthermore, a survey experiment shows that individuals with a higher body mass index prioritize cultural factors over economic ones when facing immigrants.
Keywords: J14; J15; J71; Z1; 330; Attitudes toward Immigrants; Social Identity Theory; Stigma